2000
DOI: 10.1007/pl00010638
|View full text |Cite
|
Sign up to set email alerts
|

Regular joint loading in youth assists in the establishment and strengthening of the collagen network of articular cartilage and contributes to the prevention of osteoarthrosis later in life: a hypothesis

Abstract: importance of regular joint loading in young age for the development of a well-organized and strong articular cartilage collagen network, which contributes to the prevention of OA later in life. The load-bearing properties of articular cartilage as well as the main features of the metabolism and turnover of proteoglycans (PGs) and collagen are briefly reviewed, especially in relation to joint loading. Prevention of OAThe knowledge of the pathogenesis of OA and its risk factors is today supplemented at an incre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
79
1

Year Published

2001
2001
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 87 publications
(83 citation statements)
references
References 113 publications
3
79
1
Order By: Relevance
“…The future susceptibility to injury could potentially be influenced by means of well-tailored exercise regimens, which will be of most interest in those species (human, horse) in which longterm orthopedic health is a serious concern. 13,30 Having shown that even mild exercise influenced structural and biochemical characteristics positively, it is unclear if this type of manipulation is beneficial in the long-term. Exposure to the challenges that will be faced during an athletic or working career at a young age, when collagen configuration is still being shaped, may positively influence provision of the type of collagen that is best adapted and, hence, least susceptible to injury.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The future susceptibility to injury could potentially be influenced by means of well-tailored exercise regimens, which will be of most interest in those species (human, horse) in which longterm orthopedic health is a serious concern. 13,30 Having shown that even mild exercise influenced structural and biochemical characteristics positively, it is unclear if this type of manipulation is beneficial in the long-term. Exposure to the challenges that will be faced during an athletic or working career at a young age, when collagen configuration is still being shaped, may positively influence provision of the type of collagen that is best adapted and, hence, least susceptible to injury.…”
Section: Discussionmentioning
confidence: 99%
“…Activity in early life thus may be a decisive factor for the biochemical and ultrastructural characteristics and, hence, biomechanical resistance to cartilage injury over the entire lifespan of the individual: Early exercise may be a crucial factor in the prevention of joint disease. 12,13 The aim of this study was to investigate the effects of loading pattern and exercise intensity on the (ultra)-structure of the collagen fibril network in equine articular cartilage. It was hypothesized that there would be significant differences in collagen fibril architecture in two sites, subjected to either intermittent high-intensity loading or to more continuous low-level loading.…”
mentioning
confidence: 99%
“…Although further detail will be given in a later section, it is important to note that abnormal cartilage growth and joint morphology may result from altered physical forces on the tissue during prenatal development and beyond. In addition, a number of in vivo studies with immature dogs have provided evidence that different regimes of joint loading, via exercise or limb immobilization, may lead to significant differences in articular cartilage structure (e.g., thickness), composition (e.g., proteoglycan content), and functional properties (e.g., indentation stiffness) (40).…”
Section: Growth and Maturationmentioning
confidence: 99%
“…3,4 Several treatment modalities for focal cartilage defects are based on the use of autologous tissue or cells from areas in the affected joint that are not exposed to mechanical loading. The development and maturation of articular cartilage is directed by the influence of mechanical loading, 5,6 where physiological loading steers the metabolic activity of articular chondrocytes leading to a resistance of the cartilage to the loading patterns it is exposed to. 7,8 For this reason, adult articular cartilage has distinct biochemical and biomechanical characteristics based on the differences in topographical loading within the joint.…”
Section: Introductionmentioning
confidence: 99%